Republic of Yemen - Poverty Assessment - World Bank (Washington, DC, 2012)
From what was historically known as 'Arabia Felix', a land of prosperity and happiness, Yemen has become the most impoverished among the Arab countries. The government of the united Yemen, formed in 1990, has launched so far three five-year economic reform plans with the goal of restoring Yemen's prosperity. Have these efforts succeeded? What policies are needed to further reduce poverty? The poverty assessment report aims to answer these questions. This report measures poverty in Yemen in 2005-06, and evaluates the change in poverty compared to 1998, the two years for which comparable household budget surveys are available. The period between the two survey years (1998 and 2005-06), more or less overlaps the first two five-year economic plans and captures the effect of the economic reform programs launched since 1995. In addition to measuring poverty, this report has three objectives: evaluating the role of growth and past reforms on poverty, identifying better ways to target the vulnerable poor through public action, and an assessment of the poverty monitoring system. By examining the effect of the key policies on poverty, such as the petroleum price reform and the government's social protection mechanisms between 1998 and 2005-06, the study aims to equip policy makers and development partners with the knowledge needed to improve the effectiveness of their efforts to reduce poverty in Yemen.